AUDREY’S ANXIETY DISORDER IN LANG LEAV’S SAD GIRLS: anxiety disorder, physical symptom, liar - Nurul Izzah Wahidah (AESTHETICS : Jurnal Fakultas Sastra Universitas Gresik, 2022)
This research is entitled Audrey Anxiety Disorder in Lang Leav Sad Girls, discussing the main character, Audrey who suffers from anxiety. The aims of the research is to what Audrey experiences anxiety and the consequences of Audrey's anxiety. The method used is the descriptive qualitative method. In this study, the researcher uses a psychological approach to analyze based on Sigmund Freud's theory. Disruption can be experienced by psychological factors, such as lying about something very important. Anxiety disorder episodes of causes, symptoms of anxiety disorders, and effects. After analyzing the Sad Girls novel, one of the factors for Audrey's anxiety disorder is that Audrey's emotions are depression, has descendant of lie, Audrey lying to her two best friends about the cause of lie, lying to her boyfriend, and therefore Audrey continues to live in feelings and emotions. anxiety affecting her. Audrey has physical symptoms caused by her lies, including: panic attacks, heart palpitations, stomach twisting, shortness of breath, fear, chest pain, and fainting. the cause of Audrey's anxiety was that she was lying. The result of Audrey's anxiety is meet a psychiatrist, wearing a rubber band, and moving abroad.